THE INFLUENCE OF SOCIAL SCIENCES ON THE PROFESSIONALIZATION OF SOCIAL WORK A CASE STUDY IN A TREATMENT TEAM WITH CONSUMERS OF PSYCHOACTIVE SUBSTANCES - Brinca, Joana; Morais, Nídia (Advances in Social Sciences Research Journal, 2019)
Speaking in social services implies talking about the social concept, which is an indissociable social issue and social problems arising from industrialization, urbanization and proletarization. According to ander-egg (1995b, pp. 152-153) "by the influence of sociology [and other social sciences], the term" social came to be used with two meanings: a generic and broad, referring to the global society [and the collective characteristics of a particular population] (...); and another restricted, alluding to particular questions of sociological analyses, such as social structure, social change, stratification, mobility and social participation ", that is, the individual in and in society. In the decade of 60 the "social" integrated as a partner the economic issue and improvement of the quality of life/social welfare. It was within this logic of thought that was associated with the concept "social sectors" (1995b, pp. 152-153) such as: education, housing, health, social security, culture, politics, employment. In turn, in the decade of 70, there is a change in the current paradigm. We witnessed a progressive passage/attempt to pass a tripartite intervention method to an integrated intervention method. That is, the positivism applied to the social sciences is questioned giving place to the emergence of other more integrated and more flexible paradigms highlighting the importance and influence of the social sciences in the analysis of contextual variables of social situations/ problem presented, as can be seen by the case study on the professional practice of the social worker in a treatment team of portugal, with consumers of psychoactive substances, under the opioid substitution program.